Bahaya Radikalisme terhadap NKRI - Khamid, Nur (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
An ideology, is needed by a nation to bind the people to live together in the shadeÂ of one ideology. Likewise in Indonesia that the founding fathers already set ideologyÂ of Pancasila as the nation of Indonesia, it is automatically Pancasila becomes theÂ nationâs ideology that must be obeyed and followed by the whole nations. PancasilaÂ is an ideology with the principle of âBhinneka Tunggal Ikaâ which teaches us toÂ always live with a sense of tolerance. Due to the presence of many religious, ethnic,Â racial and flow, but the essence is one also, the one nation, the nation of Indonesia.Â Lately emerged a new ideology in Indonesia that is very disturbing society, namelyÂ the ideology of radical Islam. An exclusive ideology that always puts the violence inÂ the realization of its goals. Dogmas contained in the teachings of Islam interpretednarrowly and misused to legitimize any radical action.Â The ideology of radical Islam is very much influenced by the ideology of ISIS or theÂ Islamic State in Iraq and Syria, which is a group of militant jihad idiology, that isÂ being developed all over the world through websites, books, education in schools,Â campuses, lecture , social networks like face book, you tube, twitter etc.